The characteristics of Japanese guidelines on diagnosis and treatment of cardiac sarcoidosis compared with the previous guidelines: New guidelines on cardiac sarcoidosis in Japan - Terasaki, Fumio; Kusano, Kengo; Nakajima, Takatomo; Yazaki, Yoshikazu; Morimoto, Shin-ichiro; Culver, Daniel A.; Isobe, Mitsuaki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Sarcoidosis in Japanese sarcoidosis is characterized by a high prevalence of cardiac involvement. In this regard, cardiac sarcoidosis (CS) continues to be an important focus of study among physicians caring for sarcoidosis in Japan. The Japanese Ministry of Health, Labor and Welfare (MHLW) and Japan Society of Sarcoidosis and other Granulomatous Disorders (JSSOG) have published clinical guidelines aiming to assist clinical practices. Recently, the Japanese Circulation Society (JCS) has published new clinical guidelines for the diagnosis and treatment of CS that contain several new insights compared to previously published guidelines in Japan and other countries.